2016
DOI: 10.1158/1078-0432.ccr-15-2664
|View full text |Cite
|
Sign up to set email alerts
|

BCAM and LAMA5 Mediate the Recognition between Tumor Cells and the Endothelium in the Metastatic Spreading of KRAS-Mutant Colorectal Cancer

Abstract: Purpose: KRAS mutations confer adverse prognosis to colorectal cancer, and no targeted therapies have shown efficacy in this patient subset. Paracrine, nongenetic events induced by KRAS-mutant tumor cells are expected to result in specific deregulation and/or relocation of tumor microenvironment (TME) proteins, which in principle can be exploited as alternative therapeutic targets. Experimental Design: A multimodal strategy combining ex vivo/in vitro phage display screens with deep-sequencing and bioinformatic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 50 publications
1
60
0
Order By: Relevance
“…**, P < 0.01; *, P < 0.05. 72 Reproduced with permission from ref 72 . Copyright 2016 American Association for Cancer Research.…”
Section: Figurementioning
confidence: 99%
“…**, P < 0.01; *, P < 0.05. 72 Reproduced with permission from ref 72 . Copyright 2016 American Association for Cancer Research.…”
Section: Figurementioning
confidence: 99%
“…1,2 It is expressed as a long (Lu) and a short [Lu(v13)] isoform that differ only in their cytoplasmic tail, which is 59-and 19-amino-acid residues long, respectively. Both isoforms are highly expressed during the early stages of erythropoiesis after which the expression levels strongly decline.…”
Section: Introductionmentioning
confidence: 99%
“…The previous study has shown that BCAM plays a functional role in the metastatic spreading of KRAS‐mutant colorectal cancer. Inhibition of BCAM impaired adhesion of KRAS‐mutant colorectal cancer cells specifically to endothelial cells (Bartolini et al , ). The exact mechanism of BCAM regulating GC invasion and metastasis should be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Basal cell adhesion molecule (BCAM), also known as Lutheran, is widely expressed in various tissues and is involved in many biological processes, such as cell adhesion, migration, and invasion (Bartolini et al , ; Campbell et al , ; De Grandis et al , ; El Nemer et al , ; Gauthier et al , ; Hines et al , ; Kikkawa and Miner, ; Kikkawa et al , ; Parsons et al , ). Emerging studies have shown that BCAM plays an important role in tumor progression, including skin tumors, hepatocellular carcinoma, colorectal cancer, and bladder cancer (Bartolini et al , ; Campbell et al , ; Chang et al , ; Drewniok et al , ; Kikkawa et al , ). However, the role of BCAM in GC progression is still unclear.…”
Section: Introductionmentioning
confidence: 99%